2014
DOI: 10.1111/1440-1681.12216
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and tadalafil treatment improves erectile dysfunction after spinal cord injury in rats

Abstract: Oxidative stress plays an important role both in spinal cord injury (SCI) and erectile dysfunction (ED). The present study investigated the effects of melatonin and tadalafil treatment alone or in combination on SCI-induced ED. Male Wistar albino rats (n = 40) were divided into five groups: sham-operated control and SCI-injured rats given either vehicle, melatonin (10 mg/kg, i.p.), tadalafil (10 mg/kg, p.o.) or a combination of melatonin and tadalafil. Spinal cord injury was induced using a standard weight-dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 49 publications
2
17
0
1
Order By: Relevance
“…In our previous studies with SCI-induced bladder and erectile dysfunction, we demonstrated that the damage was due inflammatory and oxidative stress mechanisms (21,27). Similarly, the results of this study also showed that SCI-induced multi-organ damage is the result of inflammation and free radicals.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In our previous studies with SCI-induced bladder and erectile dysfunction, we demonstrated that the damage was due inflammatory and oxidative stress mechanisms (21,27). Similarly, the results of this study also showed that SCI-induced multi-organ damage is the result of inflammation and free radicals.…”
Section: Discussionsupporting
confidence: 80%
“…Various studies have shown that irrespective of whether it is ischemia/reperfusion or trauma-related injuries on neural tissue or multiple organs, apoptosis has vigorously increased (32)(33)(34)(35). In our previous studies, we have shown an increase in caspase-3 activity and protein expression in SCI-induced spinal cord, bladder, and corpus cavernosum injuries (21,27,36). Moreover, an increase in renal caspase-3 activity caused by SCI demonstrated an increase in apoptosis of injured tissue while tadalafil blocked these effects (37).…”
Section: Discussionmentioning
confidence: 86%
“…The current study results showed that tadalafil pretreatment by 1, 5 or 10 mg/kg reduced caspase 3 protein expression. Similarly, Tavukçu et al (2014) in their study found that tadalafil is able to reduce caspase 3 activity, as an index of apoptosis.…”
Section: Discussionmentioning
confidence: 79%
“…Analysis of MPO, MDA and GSH was performed by a previously described method (10,11). The activity of tissueassociated MPO, a natural constituent of primary granules of neutrophils, was determined in the colonic samples homogenized in 50 mM potassium phosphate buffer.…”
Section: Tissue Mpo Activity Mda and Gsh Assaysmentioning
confidence: 99%
“…SOD activity in the colon samples was measured according to the previously described method at 460 nm (11,12). The result was expressed in SOD activity U/mg protein.…”
Section: Tissue Sod Cat and Ggt Activitymentioning
confidence: 99%